Dual-energy Spectral CT Imaging of Primary Anorectal Malignant Melanoma: A Case Report - Deng, Tie; Feng, Junbang; Wang, Wenjing; Feng, Mingjuan; Wang, Zhongrui; Li, Chuanming (Current Medical Imaging, 2024)
Background Primary anorectal malignant melanoma (ARMM) is a rare tumor. It is often misdiagnosed as hemorrhoids, polyps or colorectal cancer due to the lack of specificity of their clinical symptoms and imaging manifestations. Case Presentation In this study, we reported an 83-year-old female patient with ARMM. Computed tomography (CT) and Magnetic Resonance Imaging (MRI) showed uneven thickening of the intestinal wall about 7.0 cm from the anal margin, and no typical T1 high signal was seen on MRI. Dual-energy spectral CT showed that the effective atomic number (Zeff) of the tumor and the iodine concentration in the arterial phase (AP) and venous phase (VP) were different from other rectal malignancies reported in the previous literature. Sigmoidoscopy showed a large polypoid mass approximately 7.0 cm from the anal verge. Immunohistochemical staining showed that about 60% of Melan A and HMB-45 were positive, S-100 protein and Ki-67 were positive, and the pathological diagnosis was ARMM. Conclusion This was the first dual-energy spectral CT imaging report of ARMM. The Zeff and iodine concentration in the arterial phase and venous phase could help distinguish between ARMM and other rectal malignancies.
Keywords: ARMM